(untitled) (Knjiženstvo, časopis za studije književnosti, roda i kulture, 2023)
The Feminist Challenge to the Socialist State in Yugoslavia / Zsófia Lóránd. – Palgrave Macmillan, 2018. – 285 str. – ISBN 978-3-319-78223-2 (e-book)